Penerapan Pajak Hijau dalam Sistem Perpajakan : Tinjauan Perusahaan Manufaktur di Indonesia - Yosua Zega; Agus Munandar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to explore the application of green tax in Indonesia through manufacturing companies. The application of green tax can be viewed from the carbon generated, energy consumption and sewage by manufacturing companies. Environmental costs are a form of responsibility of manufacturing companies to the environment. This study identifies the effect of an increase or decrease in sales on the increase or decrease in carbon, energy and sewage generated. This research uses the Systematic Literature Review (SLR) method by identifying, evaluating and interpreting based on the data obtained. The results show that the government has not actively collected green taxes and has instead focused on fiscal incentive policies. The findings support that the government has yet to find a formula for green taxation.